Evaluation of Drainage Channels on Pabuaran Road Cibinong District of Bogor Regency - Jantiara Eka Nandiasa; Ridwan Adi Sanjaya (NAROTAMA UNIVERSITY, Indonesia)
Drainage can be generally defined as a technical measure to reduce excess water, whether from rain, seepage, or excess irrigation water from an area / land, so that the function of the area / land is not disturbed. This study aims to analyze, assess and evaluate the condition and capacity of the channel in the sub-district Pabuaran Road Bogor Cibinong District to discharge the flooding. Data and information used is primary data in the form of rainfall data from the Meteorology and Geophysics from the nearest irrigation hall as well as secondary data, the authors survey directly at the sites. In the flood discharge processing method using two methods of hydrograph Unit hydrograph Unit Synthetic Synthetic Nakayasu and ITB. The results of both methods is used the largest flood discharge. Getting the design flood discharge using Synthetic Unit Hydrograph ITB on Channel A of 6,434 m3 / sec. Analysis of the results of the calculation of the existing discharge chute, the discharge contained on Channel A of 2.10 m3 / sec and Channel B amounting to 0.21 m3 / sec limpas both channels experience. Alternative solutions to the problems that limpas channel or unsafe they are planning a new dimension channel.